The effects of COVID-19 on professional football: clinical management, player performance, and vaccination impact - Azzolini, E.; Favaro, A.; Colotta, F.; Volpi, P. (Journal of Science and Medicine in Sport, 2025)
The world of professional football has experienced a series of unprecedented upheavals due to the COVID-19 pandemic. From a clinical perspective, this emergency has posed significant challenges, stemming from the direct impacts of infections on athletes, and the indirect effects resulting from the cessation of activities due to lockdowns. Four years after the onset of the pandemic, a substantial body of research on elite and professional athletes has emerged, with professional footballers likely being the most extensively studied population during the COVID-19 pandemic. This has enabled the medical community to continuously adapt treatment protocols and guidelines for safe return to play (RTP) as new evidence became available. By synthesizing the latest evidence, this viewpoint aims to provide experts in sports medicine with a broad perspective that not only highlights the vast knowledge gained over these years but also stimulates critical reflection on the challenges and gaps revealed during the pandemic, identifying areas that requires further investigation and improvement, as well as guiding the development of more effective strategies and protocols to better manage future emergencies.